The omen [videorecording (DVD)] - Donner, Richard; Peck, Gregory, 1916-2003; Remick, Lee; Warner, David, 1941-; Whitelaw, Billie, 1932-2014 (Twentieth Century Fox Home Entertainment, 2000)
A chilling suspense mystery, this riveting tale of the supernatural explores the Biblical prophecy of the warning which will foretell the coming of Armageddon. The final confrontation between the forces of good and evil will begin with the birth of the son of Satan, in human form.